Cognitively Inclusive Learning: Exploring the Influence of Cognitive Styles and Gender on PGMI Students' Academic Performance - Aramudin, Aramudin; Mukarromah, Omah; Sardila, Vera; Susanti, R. Hariyani (LP. Ma'arif Janggan Magetan, 2025)
This study investigates the relationship between cognitive styles, gender, and academic performance among PGMI students, with the aim of enhancing instructional strategies. The purpose is to explore how field-independent and field-dependent cognitive styles, in conjunction with gender, influence students' academic outcomes in the Basic Social Sciences course. Employing an ex post facto research design, the study used stratified random sampling to select undergraduate students, categorized by cognitive style and gender. Cognitive styles were assessed using the Group Embedded Figures Test (GEFT), while academic performance was measured through students' grades in the course. Descriptive and inferential statistical analyses, including a two-way Analysis of Variance (ANOVA), were conducted to identify significant differences and interactions between the variables. The results indicate that field-independent students generally outperform their field-dependent peers in independent learning tasks, while gender differences reveal that male students prefer self-directed learning, while female students favor more structured guidance. The study concludes that incorporating differentiated teaching methods that address both cognitive styles and gendered learning preferences is essential for creating an inclusive learning environment that supports all students’ academic success. These findings offer valuable insights for educators in designing more effective and personalized learning experiences.